FREED INDONESIA’S CORRUPTION BETWEEN HOPE AND REALITY - Tongat Tongat; Said Noor Prasetyo (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Although the title of this article implies pessimism, but semantically title of this article is not intended to convey the message of pessimism in fighting corruptions.The title of this article actually more of reflective questions in social achievement to provide confirmation, that the eradication of corruption in Indonesia is very likely just be the "hope", but also very likely to be "true". In condition of Indonesia today, expectations and reality in eradication of corruption can be considered equally still be a tendency. At least there are a series of facts that can be used as an argumentation for an existence of two point that tendencies.